2020
DOI: 10.1002/acp.3771
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic review of experimental tests of the interrogation technique of Hanns Joachim Scharff

Abstract: Summary Hanns Scharff, an interrogator during the Second World War, was known for his remarkable effectiveness at collecting intelligence from prisoners of war using a friendly, conversational approach in which he led the prisoners to unknowingly reveal the information he wanted. In the last decade, psychologists have produced a body of experimental studies testing the effectiveness of Scharff's interrogation technique. Here, I provide a meta‐analytic review of that experimental research. The existing data sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Several suspect interviewing techniques that can facilitate credibility assessments are then evaluated, including the timing of evidence disclosure (Oleszkiewicz & Watson, 2021) and the Scharff interrogation technique (Luke, 2021). Recent research has examined both strategic and tactical approaches to the disclosure of evidence – tactics that are believed to facilitate statement‐evidence inconsistencies from guilty versus innocent suspects and to potentially facilitate the disclosure of novel information.…”
Section: Synthesizing the Investigative Interview Research Literaturementioning
confidence: 99%
“…Several suspect interviewing techniques that can facilitate credibility assessments are then evaluated, including the timing of evidence disclosure (Oleszkiewicz & Watson, 2021) and the Scharff interrogation technique (Luke, 2021). Recent research has examined both strategic and tactical approaches to the disclosure of evidence – tactics that are believed to facilitate statement‐evidence inconsistencies from guilty versus innocent suspects and to potentially facilitate the disclosure of novel information.…”
Section: Synthesizing the Investigative Interview Research Literaturementioning
confidence: 99%
“…These instructions allow research studies to mimic the typical dilemma interviewees face in actual intelligence interviews (see, e.g., Soufan, 2011). A recent review indicates that when responding to direct questions, the mock interviewee role leads participants to disclose some but not all the information they possess (Luke, 2020). We can infer from this finding that interviewees implement a honing process, at least intuitively, to determine the relevant information at their disposal.…”
Section: How Intelligence Interviewees Mentally Identify Relevant Informationmentioning
confidence: 94%
“…Anecdotes, however, are insufficient in identifying causal relationships than can inform practice. A body of research has now demonstrated the effectiveness of what has been labeled “the Scharff technique.” As reported in this issue, the full conceptualization of the technique requires further research to address research questions that remain unanswered (see Luke, 2021).…”
Section: Science As a Lens To The Past And To The Futurementioning
confidence: 99%